Fisheries Law Enforcement in the Indonesian Sea Territory - Sasvia, Hayyu (Universitas Negeri Semarang, 2019)
Indonesia has vast oceans of potential fishery resources to support the country's economy. However, this potential cannot be utilized optimally because of criminal acts in fisheries and not yet maximally law enforcement in the field of fisheries. This becomes very important and strategic in order to support the development of fisheries in a controlled manner and in accordance with the principles of fisheries management. So that fisheries development can run sustainably. The implementation of law enforcement in the field of fisheries still has weaknesses due to the complexity of the fisheries crime problem, as well as the problem of coordination mechanisms between law enforcement agencies and the establishment of unfair fisheries courts in all jurisdiction countries. In solving the problem, reform in law enforcement is the main key which focuses on legal substance and human resources that support law enforcement in the field of fisheries so that fisheries development can run in a sustainable manner.